Rethinking of Public Secondary Schools Discipline in Kenya - Nandeke, Erick; Chumba, Sammy K.; Kiprop, Catherine (European Scientific Journal, ESJ, 2017)
Student Council is a representative structure through which students in a secondary school become involved in school affairs. The study set out to investigate student council participation in the management of discipline in public secondary schools in Teso North Sub-County in Busia County, Kenya. The study sought to establish: the influence of student council participation in the formulation of rules and regulations on management of discipline, and the influence of student council involvement in formulating punishment on the management of discipline. The target population was 7379 students and 189 teachers and 27 principals from 27 schools. The research employed descriptive survey design using a random sample of 365 students, 18 teachers and 9 principals. This sample size was determined using Krejcie and Morgan’s table of sample determination and using coefficient variation of 30% and a standard error of 2% through stratified simple random sampling technique. The data was collected using a selfadministered questionnaire. The study established that schools involved students in designing punishment but students never took punishment positively and that common disciplinary problems experienced in schools was due to lack of students involvement. It was further established that students were haphazardly involved in the school management of students’ discipline. Thus the study recommends schools to empower students’ council in which students’ views and ideas are heard and discussed; Ministry of education to organize and offer seminars where school heads are well sensitized on involving students in school management.